A Case-Control Study of Environmental Risk Factors for Pulmonary Tuberculosis: Housing Density, Indoor Humidity, and Smoking Habits - Ilham Rahmatullah; Sulung Alfianto Akbar; Rosi Susilawati (JURNAL INFO KESEHATAN, 2025)
Pulmonary tuberculosis (TB) remains a major public health problem in urban settings and is strongly influenced by environmental and behavioral factors. This study aimed to examine the effects of housing density, indoor humidity, and smoking behavior on the incidence of pulmonary TB in the working area of the Segiri Health Center, Samarinda. An observational analytic study with a case–control design was conducted involving 50 respondents, consisting of 25 TB cases and 25 matched controls. Data were collected through structured interviews, direct observation, and environmental measurements, and were analyzed using chi-square tests and odds ratios. The results indicated that high housing density was significantly associated with an increased risk of TB (OR = 11.16; p = 0.001), while smoking behavior was also significantly related to TB incidence (OR = 5.63; p = 0.010). High indoor humidity showed an increased risk but was not statistically significant. In addition, a large proportion of TB cases were frequently exposed to secondhand smoke in enclosed spaces. In conclusion, high housing density and smoking, including exposure to secondhand smoke, are key determinants of pulmonary TB incidence, whereas indoor humidity demonstrated a weaker association. These findings highlight the importance of improving housing conditions and strengthening tobacco control efforts as part of TB prevention strategies in urban areas.